Valuation of Small-Sized Company a Multiparadigmatic Approach in Brazil - Vaz da Fonseca, Peter (Archives of Business Research, 2019)
Assets valuations are necessary for purposes of investment, decision making and historical performance measurement. Companies’values are standardized claimings tending to be dynamically traded in capital markets, where transaction prices may be observed. Evaluation is a set of procedures to get the economical value of an asset which is used by financial market participants aiming at establishing the amount they may pay or receive for a certain business. Obtaining valuations, for small private companies is a chalenge as there is not a stock market from which a value reference can be obtained and also for its own features, in general heterogenous. Under the interpretativist perspective, company evaluation considers the aspects considered as relevant by investors